On Congruent Domination Number of Disjoint and One Point Union of Graphs - S. K. Vaidya; H. D. Vadhel (IndoMS, 2022)
A dominating set D V(G) is said to be a congruent dominating set of G if _v V(G) d(v) 0 ( _v D d(v)).The minimum cardinality of a minimal congruent dominating set of G is called the congruent domination number of G which is denoted by γ_cd(G). We establish the bounds on congruent domination number in terms of order of disjoint union of graphs as well as one point union of graphs.